"Absolute trash can" / Abdul Fatah Hasan Kashfi, Ahmad Farizzuan Abdul Halim and Mario Joseph - Kashfi, Abdul Fatah Hasan; Abdul Halim, Ahmad Farizzuan; Joseph, Mario (2016)
This product is known as Absolute Trash Can (ATC). The ATC is a hands-free trashcan which will automatically open the lid when the sensor detect object above the lid. Furthermore, the ATC have a sensor which will notify the consumer when the trash bag is full. It contain natural activated charcoal odors absorbs that effectively eliminate unpleasant smells occupied within it. The ATC is built with trash bag removal system where its function is to tie the trash bag and remove the trash bag outside the trashcan automatically.